(untitled) (Fiep Bulletin - online, 2016)
INTRODUCTION: The science of nursing has a wide scientific structure, and the Nursing Consultation/Nursing Process is one of the assistance tools used in the clinical practice, aiming at the solutions of the problems found in the client (RIBEIRO e MACIEL, 2011). OBJECTIVES: To check the perception of the professional nurse before the diagnosis process. MATERIALS AND METHODS: It is a field, descriptive, and exploratory of quantitative approach research. RESULTS AND DISCUSSIONS: The analysis of the testimonials given by the nurses, resulted in themes, which were organized into 2 categories: I – Performance of the professional nurse facing the execution of the nursing diagnosis in the clinical practice and its importance, II – Execution of the diagnosis process in the clinical practice and 3 subcategories such as: I.I. Knowledge of the nursing professional facing the diagnosis process in the clinical practice, II.I Difficulties and II.II Abilities. In the category I and subcategory II it was possible to identify in the testimonials given by the professionals the importance of having a diagnosis, as it is a tool that will guide the nursing care individually based on the necessity seen in the patient. Whereas in the category II subcategory: II.I about difficulty, it was evident in the testimonials given by the professionals the lack of time and human resources as the most highlighted reason that may impair the applicability of the nursing diagnosis. In the subcategory II.II abilities, the professionals emphasized the need for theoretical and practical knowledge for application of the nursing diagnosis, as well as clinical thinking, which are essential during the evaluation of the patient by the professional nurse. CONCLUSION: In conclusion, the nurses think it is important to apply the nursing diagnosis process, yet it is still a challenge to be fulfilled, due to the difficulties found and the need for abilities for its execution.